2021
DOI: 10.1002/er.6455
|View full text |Cite
|
Sign up to set email alerts
|

Ab‐initio study of opto‐electronic and thermoelectric properties of direct bandgap double perovskites Rb 2 XGaBr 6 (XNa, K)

Abstract: Double perovskite halides are potential materials for the production of renewable energy that could meet the global demands for resolving energy shortage issues. In this study, we systematically investigate the Rb 2 XGaBr 6 (X Na, K) double perovskites using the full-potential linearized augmented plane wave (FP-LAPW+lo) method of density functional theory. The thermodynamic as well as the structural stabilities of the studied materials have been confirmed from the calculated formation energy and Goldsmith tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Where r , A r B r X are the radius of Cs + , the mean radius of sites B + and B +3 and radius of halides respectively. [17]. The estimated tolerance, octahedral and modified tolerance factors are reported in table 1.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…Where r , A r B r X are the radius of Cs + , the mean radius of sites B + and B +3 and radius of halides respectively. [17]. The estimated tolerance, octahedral and modified tolerance factors are reported in table 1.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…Among DPHs, recently Li-based DPHs Li 2 CuBiZ 6 (Z=Cl, Br and I) and Li 2 AgGaX 6 (X = Cl, Br, I) explored theoretically for the manufacturing of optoelectronic and thermoelectric device applications using density functional theory [13,14]. Their finding of direct bangap nature indicate all DPHs potential candidate for photovoltaic devices.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Haq et al predicted that Rb 2 XGaBr 6 (X = Na, K) are promising photovoltaic and thermoelectric materials due to their optimum optical absorption coefficient and large ZT values, respectively. 52 Later, Iqbal et al have shown the emerging photovoltaic and thermoelectric properties of Rb 2 AlInX 6 (X = Cl, Br, I) due to their narrow band gap. 53 Also, Nawaz et al reported that Rb 2 YInX 6 ( X = Cl, Br, I) are thermodynamically stable and they are suitable for photovoltaic and thermoelectric technology.…”
Section: Introductionmentioning
confidence: 99%